1989
DOI: 10.1111/j.1559-1816.1989.tb01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Contraceptive Efficacy: A Discriminant Analysis of Three Groups of Adolescent Women1

Abstract: The relationship of knowledge and attitudes to adolescent contraceptive efficacy was investigated in a multivariate study, with demographic and sexual history variables covaried. Subjects were unmarried, sexually active 15‐ to 19‐year‐old women. Two studies were conducted: one using a large and representative sample and the second using a smaller, high socioeconomic status sample that is more typical of samples generally used in earlier research. Subjects were classified as effective, ineffective, or nonusers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…According to social comparison theory (Festinger, 1954) and social impact theory (Latane, 1981), socially proximal comparison groups are more relevant and have greater influence than more distal comparison targets. In addition, previous research has suggested that specific, relevant attitudes are better predictors of behavior (Kim & Hunter, 1993;Morrison, 1989) than attitudes toward a general concept (Ajzen, 1982;Ajzen & Fishbein, 1977). For example, perceptions of close friends' drinking norms have been demonstrated to be more precise, as well as more salient, to college students and have been shown to be a better predictor of alcohol consumption compared to perceptions of typical student drinking norms or perceptions of gendernonspecific drinking norms (Baer et al, 1991).…”
Section: Gender Differences In Normative Misperceptionsmentioning
confidence: 99%
“…According to social comparison theory (Festinger, 1954) and social impact theory (Latane, 1981), socially proximal comparison groups are more relevant and have greater influence than more distal comparison targets. In addition, previous research has suggested that specific, relevant attitudes are better predictors of behavior (Kim & Hunter, 1993;Morrison, 1989) than attitudes toward a general concept (Ajzen, 1982;Ajzen & Fishbein, 1977). For example, perceptions of close friends' drinking norms have been demonstrated to be more precise, as well as more salient, to college students and have been shown to be a better predictor of alcohol consumption compared to perceptions of typical student drinking norms or perceptions of gendernonspecific drinking norms (Baer et al, 1991).…”
Section: Gender Differences In Normative Misperceptionsmentioning
confidence: 99%
“…The sequence of choices, which may be explicit or implicit, active or passive, is: whether to initiate sexual activity; whether to continue it; whether to practice contraception and, if so, how diligently; and once pregnant, whether to abort, marry the father, place the child for adoption, or bear the child as an unmarried mother. Studies taking this approach include Cvetkovich and Grote (1980), Brazzell and Acock (1988), and Morrison (1989). Cvetkovich and…”
Section: Previous Research On Attitudes and Premarital Childbearingmentioning
confidence: 99%
“…Other studies found liberated girls less likely to initiate sexual activity (Cvetkovich and Grote, 1980) and more likely to practice effective contraception (Morrison, 1989). These tendencies would reduce the chances of premarital pregnancy.…”
mentioning
confidence: 99%
See 2 more Smart Citations